2016
DOI: 10.1242/bio.021519
|View full text |Cite
|
Sign up to set email alerts
|

REV-ERBα regulates Fgf21 expression in the liver via hepatic nuclear factor 6

Abstract: The circadian clock contributes to the timing of many body functions including metabolism and reproduction. The hepatokine fibroblast growth factor 21 (FGF21) is a critical metabolic regulator involved in modulation of fertility. Here we show that lack of the clock component REV-ERBα elevates FGF21 levels in liver and plasma. At the molecular level, REV-ERBα modulates the expression of FGF21 via the liver-specific hepatic nuclear factor 6 (HNF6). We conclude that REV-ERBα regulates metabolism and reproduction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…A study reported that Fgf21 expression is circadian in the liver, peaking during the fasting phase and under direct control of the circadian machinery 138 . However, transactivation of Fgf21 by BMAL1/CLOCK was not confirmed by an independent study 139 and serum levels of FGF21 are relatively stable under normal feeding regimens 137 , displaying a 24-h oscillatory pattern only following prolonged fasting 140, 141 . Nevertheless, FGF21 is able to modulate directly the central clock by activating β-Klotho signaling in the SCN.…”
Section: Metabolic Coupling Of Central and Peripheral Clocksmentioning
confidence: 91%
“…A study reported that Fgf21 expression is circadian in the liver, peaking during the fasting phase and under direct control of the circadian machinery 138 . However, transactivation of Fgf21 by BMAL1/CLOCK was not confirmed by an independent study 139 and serum levels of FGF21 are relatively stable under normal feeding regimens 137 , displaying a 24-h oscillatory pattern only following prolonged fasting 140, 141 . Nevertheless, FGF21 is able to modulate directly the central clock by activating β-Klotho signaling in the SCN.…”
Section: Metabolic Coupling Of Central and Peripheral Clocksmentioning
confidence: 91%
“…It is also known that FGF21 has signaling connections to some important regulators of circadian metabolism, e.g. AMPK [127] and REV-ERBα [128]. Adiponectin, a target gene of FGF21 signaling, is under the circadian regulation [129].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…FGF21 exhibits a diurnal rhythm in ( 52 , 53 ) and humans ( 54 ), and overexpression of FGF21 disrupts circadian locomotor behavior via hypothalamic Klb ( 33 ). Bookout et al ( 33 ) showed that overexpression of FGF21 reduces total running wheel behavior, with an increase in light phase activity, both of which are normalized in mice deficient for central Klb .…”
Section: Discussionmentioning
confidence: 99%